Efficacy and safety of transcutaneous electrical nerve stimulation (TENS) for acute and chronic pain in adults: a systematic review and meta-analysis of 381 studies (the meta-TENS study) - Gareth Jones; Mark I. Johnson; Carole A. Paley; Matthew R. Mulvey; Priscilla G. Wittkopf (BMJ Open)
Objective To investigate the efficacy and safety of transcutaneous electrical nerve stimulation (TENS) for relief of pain in adults.Design Systematic review and meta-analysis.Data sources Medline, Cochrane Central, Embase (and others) from inception to July 2019 and updated on 17 May 2020.Eligibility criteria for study selection Randomised controlled trials (RCTs) comparing strong non-painful TENS at or close to the site of pain versus placebo or other treatments in adults with pain, irrespective of diagnosis.Data extraction and synthesis Reviewers independently screened, extracted data and assessed risk of bias (RoB, Cochrane tool) and certainty of evidence (Grading and Recommendations, Assessment, Development and Evaluation). Mean pain intensity and proportions of participants achieving reductions of pain intensity (≥30% or >50%) during or immediately after TENS. Random effect models were used to calculate standardised mean differences (SMD) and risk ratios. Subgroup analyses were related to trial methodology and characteristics of pain.Results The review included 381 RCTs (24 532 participants). Pain intensity was lower during or immediately after TENS compared with placebo (91 RCTs, 92 samples, n=4841, SMD=−0·96 (95% CI −1·14 to –0·78), moderate-certainty evidence). Methodological (eg, RoB, sample size) and pain characteristics (eg, acute vs chronic, diagnosis) did not modify the effect. Pain intensity was lower during or immediately after TENS compared with pharmacological and non-pharmacological treatments used as part of standard of care (61 RCTs, 61 samples, n=3155, SMD = −0·72 (95% CI −0·95 to –0·50], low-certainty evidence). Levels of evidence were downgraded because of small-sized trials contributing to imprecision in magnitude estimates. Data were limited for other outcomes including adverse events which were poorly reported, generally mild and not different to comparators.Conclusion There was moderate-certainty evidence that pain intensity is lower during or immediately after TENS compared with placebo and without serious adverse events.PROSPERO registration number CRD42019125054.